The 1960s - Healey, Tim (Franklin Watts London, 1988)
Provides a photographic history of the decade touching on important issues and events. Includes a chronology and personalities section. Looks at the sixties, including the civil rights and anti-war movements, the Berlin Wall, the Kennedy and King assassinations, the Vietnam War, Woodstock, and the moon landings
Includes index
Keywords: Nineteen sixties -- Pictorial works -- Juvenile literature; Manners and customs; History, Modern -- 1945- -- Civilization